Impact of in-hospital medical management for COVID-19 pandemic on door-to-balloon time in patients with ST-elevation myocardial infarction. (3rd October 2022) - Takasaki, A; Kurita, T; Yanagisawa, M; Ino, A; Hiramatsu, D; Ikmi, A; Ito, H; Kato, T; Fukuoka, S; Sugimoto, T; Nakata, T; Masuda, J; et al.
Abstract: Background: Delayed door-to-balloon (DTB) time and deterioration of in-hospital mortality during the coronavirus disease 2019 (COVID-19) pandemic have been reported. Little is known about the impact of changes in in-hospital medical management before primary percutaneous coronary intervention (PCI) for COVID-19 such as screening test (antigen or polymerase chain reaction (PCR) tests, chest CT for excluding the pneumoniae) and primary PCI under full personal protective equipment (PPE) on DTB time and in-hospital mortality. Purpose: The purpose of this study was to evaluate the impact of in-hospital medical management for COVID-19 on DTB time and in-hospital mortality during COVID-19 pandemic period. Methods: We compared DTB time and in-hospital mortality of 502 ST-elevation myocardial infarction (STEMI) patients during COVID-19 pandemic (February 2020 and January 2021) with 2035 STEMI patients before pandemic (February 2016 and January 2020) using date from Mie ACS registry, a retrospective and multicenter registry. Results: The COVID-19 screening tests before primary PCI and/or primary PCI under full PPE was performed on 173/502 (34.5%) patients (antigen or PCR tests; 39 (7.8%), chest CT; 156 (31.3%), full PPE; 11 (2.2%)). These patients had lower rate of achievement of DTB time ≤90 min compared with others (Figure 1A). Moreover, In-hospital management of COVID-19 screening tests and/or primary PCI under full PPE was an independent factor of DTB time>90 min with odds ratio of 1.94 (95% confidential interval: 1.37–2.76, p<0.001). In addition, in-hospital mortality of those patients was higher compared with others (Figure 1B). Conclusion: In-hospital medical management for COVID-19 screening tests before primary PCI and/or primary PCI under full PPE was the independent factor of DTB time>90 min. This study reinforces the need to focus efforts on shortening DTB time, while controlling the epidemic of infection. Funding Acknowledgement: Type of funding sources: None.